Der må være en kant. En diskussion af forskellige opfattelser af rum og virkelighed i lyset af Kants teori om rummet - Madsen, Henrik (Tidsskriftet Antropologi, 2019)
This article discusses to what extent is makes sense to talk about different conceptions of space, and different experiences of space. According to Kant our sense perceptions are organized by a unique set of categories and by the form of our inner and outer sense, time and space respectively. To Kant, this spatial intuition is culturally invariant because it is a condition for the possibility of any experience whatsoever. Without accepting Kant’s terminology the author agrees that certain rudimentary abilities of spatial orientation have to be presupposed as universally shared. However, we do seem to have different ways of conceiving and thinking about space. Within our own culture we can distinguish between subjective/personal, public/official and scientific conceptions of space. It is argued that in other cultures, where these conceptions are different, we should be weary of a quasi-Kantian position which attributes such differences to differences in ‘categorial schemes’, and which further claims that these are conditions for the possibility of experience in this specific culture. Such a culturally speciftc a priori category confuses conditions for any possible experience with possible experiences. Furthermore, it ignores epistemological distinctions we readily employ within our own cultures.